2018
DOI: 10.1016/j.neuropharm.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 confers neuroprotection via promotion of glutamate transporters in a mouse model of Parkinson's disease

Abstract: Ginsenoside Rb1 has been demonstrated to protect dopaminergic (DA) neurons from death in vitro. However, the neuroprotective effects and underlying mechanism of Rb1 in treating Parkinson's disease (PD) remain uncharacterized. In this study, we explored the effects of Rb1 on the movement disorder and the underlying mechanisms based on the glutamatergic transmission and excitotoxicity in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD. Here, for the first time, we report that Rb1 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 83 publications
4
46
0
Order By: Relevance
“…Taken together, these findings indicated that ginseng exhibits its neuroprotective properties and improves is could be due to the presence of bioactive compound ginsenosides in ginseng. Several studies have reported on the neuroprotective effect of ginsenosides, particularly ginsenosides Rg1, in various neurodegeneration models [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…Taken together, these findings indicated that ginseng exhibits its neuroprotective properties and improves is could be due to the presence of bioactive compound ginsenosides in ginseng. Several studies have reported on the neuroprotective effect of ginsenosides, particularly ginsenosides Rg1, in various neurodegeneration models [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…The ginsenoside Rb1 has been widely assessed for its neuroprotective features [66]. While most experiments used a limited number of doses, several papers reported hormetic-biphasic dose responses for Rb1.…”
Section: Alzheimer's and Parkinson's Diseases And Stroke Modelsmentioning
confidence: 99%
“…Rb1 treatment ameliorated MPTP-induced motor impairment, protected dopaminergic neuron death, and suppressed α-synuclein expression and astrogliosis in mouse. It increased glutamate transporter expression through nuclear translocation of NF-κB, regulated glutamate receptor expression, and promoted synaptic protein expression [ 73 ]. Two major pharmacological effects of ginsenoside Rb1 on cognitive impairment are shown in Figure 2 .…”
Section: Pharmacological Potential Of Active Ginseng Constituents In mentioning
confidence: 99%